2013
DOI: 10.1021/jo402212j
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalytic Reactions of α-Trifluoromethylated Esters with Terminal Alkenes at Room Temperature

Abstract: CF3-containing esters smoothly reacted with electron-deficient alkenes in the presence of a phosphine (2-dicyclohexylphosphino-2',4',6'-triisopropylbiphenyl) organocatalyst at room temperature in an aerobic atmosphere. These Michael reactions efficiently provided products with a CF3 quaternary carbon center.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 75 publications
(30 reference statements)
0
9
0
Order By: Relevance
“…Evaluation of the NMR spectra indicate, among repeating units from oxa-Michael and transesterification reactions, 28,29 the presence of Rauhut-Currier derived linkages. 30,31,32 This repeat unit is characterized by peaks at 6.22 and 5.64 ppm in the 1 H-NMR spectrum and at 126.6, 33.0, 27.3 ppm in the 13 C-NMR spectrum of poly4 (see Supporting Information) and its share is with approximately 17-20% higher in polymers prepared at 80 °C (Figure 2). The formation of this repeat unit consumes two equivalents of acrylates and thus, disproportionally decreases the quantity of acrylate groups in relation to alcohol groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluation of the NMR spectra indicate, among repeating units from oxa-Michael and transesterification reactions, 28,29 the presence of Rauhut-Currier derived linkages. 30,31,32 This repeat unit is characterized by peaks at 6.22 and 5.64 ppm in the 1 H-NMR spectrum and at 126.6, 33.0, 27.3 ppm in the 13 C-NMR spectrum of poly4 (see Supporting Information) and its share is with approximately 17-20% higher in polymers prepared at 80 °C (Figure 2). The formation of this repeat unit consumes two equivalents of acrylates and thus, disproportionally decreases the quantity of acrylate groups in relation to alcohol groups.…”
Section: Resultsmentioning
confidence: 99%
“…9,10,11 Accordingly, triarylphosphines are generally less reactive in conjugate additions than trialkylphosphines and often high catalyst loadings of up to 20 mol% and elevated temperatures are necessary to obtain satisfactory conversions. 4,12,13 The low reactivity of arylphosphines can be enhanced by introducing electron donating groups (e.g. -CH3, -OMe, -NMe2) at the aryl moieties.…”
Section: Introductionmentioning
confidence: 99%
“…23 a The notorious C–F bond cleavage of α-trifluoromethyl carbanions competes with other types of transformations in organic synthesis. 125 These interesting properties of C–F bonds could be partially understood in terms of electrostatic/dipole interactions, which were summarized by O'Hagan. 11 To facilitate the C–F bond cleavage step and its defluorination application on the synthesis of heterocyclic compounds, some general principles for C–F bond activation and utilization are highlighted.…”
Section: Discussionmentioning
confidence: 99%
“…The reaction is mild enough to apply to aldimines having the AcO−, TBDMSO−, or MeS− group. LiCl-catalyzed synthesis of β-amino esters 91 via Mannich reaction Wang et al 211 reported 2-dicyclohexylphosphino-2,4,6-triisopropylbiphenyl (XPhos, a phosphine derivative, 93)-catalyzed Michael addition of α-trifluoromethylated ester (92) with α,β-unsaturated ketone (26) in N,N-dimethyformamide (DMF) under an aerobic atmosphere at room temperature resulting to the generation of a series of γ-substituted α-trifluoromethylated ester derivatives (94) with moderate to good yields (Scheme 34). 210 Scheme 33.…”
Section: Addition Reactionsmentioning
confidence: 99%